Julius Kaiser's analytic-synthetic method: Pioneering for the subject approach to information - Sales, Rodrigo de; Chaves Guimaraes, Jose Augusto [UNESP] (Pontificia Universidade Catolica Campinas, 2017)
The development of the analytic-synthetic method, normally attributed to S.R. Ranganathan, had its initial foundation defined in the systematic indexing developed by J.Kaiser at the beginning of the 20th century, some two decades prior to the appearance of the faceted classification. This study aims to support the proposition that by combining the philosophical principle of categorization (for analysis) with the pragmatic logic of indexing of subjects (for synthesis), as Kaiser elaborated his form of indexing, he conceived the underpinning bases for the analytic-synthetic method. The theoretical table which subsidized the study is comprised of the bibliography pertinent to the subject approach to information, particularly regarding bibliographic classification, subject cataloguing and indexing. Using William James's pragmatism as our methodological approach, we investigated how the procedural systematics of Kaiser's indexing method emerges as a forerunner to the analytic-synthetic method. The fundamental elements of the investigation were the analysis of components, conduction of analysis, synthesis and products of the synthesis, thus including the analytic and synthetic dimensions of the works carried out by Kaiser and Ranganathan.
Keywords: Classification of the two points; Faceted classification; Analytic-synthetic method; Subject tratament of Information